Prevalence of incontinence in patients after stroke during rehabilitation: A multi-centre study - Apichana Kovindha (2018)
Objective: To report the prevalence and degree of isolated urinary and faecal incontinence and double incontinence (i.e. both urinary and faecal incontinence) in patients after stroke during post-acute rehabilitation and the factors related to incontinence. Design: A multi-centre prospective study. Methods: Data were extracted from the Thai Stroke Rehabilitation Registry. A total of 185 patients admitted within 4 weeks post-stroke were recruited. Based on the Barthel Index of Activities of Daily Living, the prevalence and degree of isolated urinary incontinence or faecal incontinence, and double incontinence were reported. Multivariate analysis was performed to identify any factors related to incontinence. Results: The admission prevalence for isolated urinary incontinence was 12.4%, for isolated faecal incontinence 7.6% and for double incontinence 33%. At discharge, the prevalence had decreased, to 8.1% for isolated urinary incontinence, 4.9 % for isolated faecal incontinence and 15.1% for double incontinence. Cognitive (adjusted odds ratio (OR) 3.63; 95% confidence interval (CI) 1.71-7.70) and leg muscle functions impairments (adjusted OR 2.79; 95% CI 1.29-6.07) were significantly related to urinary incontinence; whereas, age (adjusted OR 1.98; 95% CI 1.07-3.67) was related to faecal incontinence at admission. Conclusion: Double incontinence was more prevalent than isolated incontinence in patients after stroke during post-acute rehabilitation. The decrease in prevalence at discharge reflected a recovery of bladder and bowel control. Age, cognitive and leg motor function impairments were related to incontinence. © 2009 The Authors.